THE EFFECT OF CONVENIENCE, TRUST, SERVICE QUALITY, AND APPLICATION FEATURES ON CUSTOMER SATISFACTION AMONG GENERATION Z USERS OF LIVIN’ BY MANDIRI IN SEMARANG CITY - Mirasanti Wahyuni; Eka Novita Sari; Aris Sunindyo (Applied Accounting and Management Review (AAMAR), 2026)
This study aims to analyze the simultaneous and partial effects of convenience, trust, service quality, and application features on customer satiscation among Generation Z users of Livin’ by Mandiri in Semarang City. In today’s modern era, mobile banking services have become an essential offering by banks to facilitate customers in conducting transactions. Data was collected through a questionnaire method from 100 respondents who are users of Livin’ by Mandiri among Generation Z in Semarang City. The data analysis model uses the Multiple Linear Regression Analysis Model. Meanwhile, the data analysis techniques used the f test, t test, and Coefficient of Dtermination (R2) test. The results indicate that convenience and trust partially have a significant impact, while service quality and app features partially do not have a significant impact on customer satisfaction among Generation Z users of Livin’ by Mandiri in Semarang City. Simultaneously, convenience, trust, service quality, and app features have a significant impact on customer satisfaction among Generation Z users of Livin’ by Mandiri in Semarang City.